STRATEGI MENINGKATKAN KINERJA KOPERASI SEKOLAH - Rahmawati, Ushi; Septiningsih, Alvian Septiningsih; Istighnaul Fitria, Zidna Istighnaul Fitria; Zaki’adani, Muhammad; Siswadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the midst of its strategic role as a means of entrepreneurial learning and strengthening the school economy, school cooperatives still face various challenges which cause their performance to not be optimal. This is caused by various factors such as weak management, low member participation, limited capital, and an administrative system that is not well organized. This research aims to analyze the performance of school cooperatives, identify influencing factors, and formulate strategies for improving the performance of school cooperatives. This research uses a qualitative approach with descriptive methods. The data sources used are secondary data obtained from books, scientific journals and relevant documents. The data collection technique is carried out through documentation studies, while data analysis uses the stages of data reduction, data presentation, and drawing conclusions. The research results show that the performance of school cooperatives is influenced by the quality of management, member participation, capital adequacy, and administrative and financial systems. Strategies for improving cooperative performance can be carried out through strengthening management, increasing member involvement, effective capital management, and implementing a transparent and accountable administration system. Apart from that, service innovation and improving facilities are also important factors in attracting member interest and increasing the sustainability of school cooperatives.